Pengaruh Kompensasi terhadap Kepuasan Kerja, Motivasi dan Kinerja Perusahaan (Studi pada PDAM di 8 dan Propinsi, Indonesia) - Sjamsi, Nurus (Universitas Brawijaya, Indonesia, 2008)
Problems of PDAM now a days as a BUMD mostly are low performance and loss which is experienced in almost each operational year. Company performance, observed from its relationship with leadership which is influenced by compensation policy, can create job satisfaction and motivate that leader. Leadership, in its activities will result attitude style, show leadership style, and the managerial competence of a leader in order to influence organizational performance. The goal of this research is to reveal: (i) the strength of the influnce of compensation toward job satisfaction, leader motivation, and company performance, (ii) the strength of the influence of leadership style in the perception of leadership style: transactional, transformational, and servant, toward company performance. The institutional unit analysis, sampling frame is the direction of PDAM in eight provinces in Indonesia, include 108 PDAM. The respondents in this research are 324. Response rate is 48,15% from 52 PDAM. The survey method is used to measure the respondent perception. The sampling technique is using closed and open questionnaires, and interview is based on the Purposive Sampling Quota by sub group the populations. Statistical analysis is used to test the hypothesis using the model Structural Equition Model (SEM). The findings of this research are: (i) the appearance of differing variables between the the groups of leaders and of non-leaders in its relationship with the company performance, which is the servant leadership style, (ii) compensation strategy which influences job satisfaction can motivate leaders dan reach their goals only through the practice of servant leadership style, and (iii) compensation which influences extrinsic and intrinsic of company leaders then influences transactional leadership style specifically.